Economía social y solidaria en el distrito metropolitano de Quito :Experiencias y ejes para una política pública municipal en el caso de los barrios la Pradera, Turubamba, Venecia - Reyes Encalada, Ángel Bladimir (2015)
In Chapter 1 theories and definitions of the capitalist economy and social economy are presented, the more general aspects of one and another way of doing economics are analyzed and their features and elements are compared, capitalism is questioned as a natural economic base, universal and irreversible and solidarity economy is highlighted as a tool to serve the community in their quest towards a more coherent and complete satisfaction of their needs. In chapter 2 the experiences of popular and solidarity economy in Latin America and Ecuador are described, the organizational experiences mentioned are varied and correspond to a process of highly creative social experimentation that in some way or another have been strengthened, an analysis of the formation of the National Constituent Assembly 2008 is performed and important elements of the legal framework of solidarity economy, protected in the Ecuadorian constitution, and sectoral and zonal agendas are detailed.